The Child Marriage Trends in 3T Regions of Sumatra: The Impact of Law No. 16/2019 and the Covid-19 Pandemic on Poor Communities - Wahyuni, Budi; Nur, Ratih Hidayah; Purwatiningsih, Sri (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2024)
The study